2020
DOI: 10.1021/acs.accounts.0c00482
|View full text |Cite
|
Sign up to set email alerts
|

Sulfono-γ-AApeptides as Helical Mimetics: Crystal Structures and Applications

Abstract: Conspectus Foldamers have defined and predictable structures, improved resistance to proteolytic degradation, enhanced chemical diversity, and are versatile in their mimicry of biological molecules, making them promising candidates in biomedical and material applications. However, as natural macromolecules exhibit endless folding structures and functions, the exploration of the applications of foldamers remains crucial. As such, it is imperative to continue to discover unnatural foldameric architectures with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 49 publications
(119 reference statements)
0
81
0
Order By: Relevance
“…Thus, it is reasonable to consider sulfonopeptides or peptides with certain sulfonamide moiety as potential medicinal candidates. Recently, N-sulfonylated peptides 106 and the modification of the sulfonamidecontaining peptides 107,108 have been paid more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable to consider sulfonopeptides or peptides with certain sulfonamide moiety as potential medicinal candidates. Recently, N-sulfonylated peptides 106 and the modification of the sulfonamidecontaining peptides 107,108 have been paid more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inhibiting the p53–hDM2 interactions, β 3 -peptide has also been developed to serve as HIV fusion inhibitors. They further developed a β 3 -decapeptide with a non-natural trifluoromethylbenzene side chain that inhibited the HIV gp41-mediated fusion with a CC 50 /EC 50 ratio of 8, a major improvement compared to previous works. , Cai et al developed an impressive class of sulfono-γ-AApeptides that can reproducibly fold into well-defined helical structures. They demonstrated that these sulfono-γ-AApeptide helices were excellent mimicries of α-helices in several therapeutically relevant protein–protein interactions and could serve as inhibitors or agonists to these interactions, such as BCL9-β-catenin, p53-MDM2/MDMX, and glucagon peptide-GLP-1R. …”
Section: Functional Applications Of Sequence-controlled Polymersmentioning
confidence: 99%
“…Over the last few decades, conformationally well‐defined short peptides have been intensively studied to design peptide‐based drugs [ 1–2 ] and organic functional materials. [ 3–4 ] In particular, the helical peptide foldamers composed of nonproteinogenic amino acids have attracted enormous attention because they possess a strong tendency to adopt a robust helix with a relatively small number of residues (6–8 residues) in solution. [ 5–9 ] Since the foldamer's helical types that originate from intramolecular hydrogen‐bonding patterns are predictable and controllable at the molecular level, more sophisticated structures that are not found in nature can be designed with foldamers from scratch.…”
Section: Introductionmentioning
confidence: 99%